The truth about managing change : the essential truths in 20 minutes - Kane, William S. (Truth about (FT Press), 2008)
Praise for The Truth About Thriving in Change "Although we know that change is constant, we are always surprised by it. Bill provides a roadmap to successfully navigate corporate change. Being conscientious to follow the 'Truths' will enable people to successfully face any organizational challenge." Rosina Racioppi, President and Chief Operating Officer, WOMEN Unlimited, Inc. "A must read for managers, Bill uses language with care, economy, and precision. Managing change is basically about helping people deal with uncertainty. This writing effectively uses a combination of practical experience, common sense, and humor in describing strategies designed to achieve desired results while maintaining morale and enhancing engagement." Michael Mimnaugh, Vice President, Human Resources, Sony Corporation of America "Many students are under the impression that a graduate degree will impart all wisdom, but what they fail to recognize is that there is no substitute for experience. What Bill's book does so well is to impart his substantial experience--along with the textbook knowledge--to move you ahead in your career. If you manage people or projects, the wisdom found within each 'Truth' will help keep you on the leading edge of your profession. This is a reference guide that belongs in your library." Stuart J. Lipper, Senior Director of MBA Programs, Rutgers Business School, Rutgers, The State University of New Jersey Everything you need to know to drive and sustain successful change ... what really works! · The truth about transforming organizations without destroying morale · The truth about why your way may not be the best way · The truth about creating a cultural framework for long-term success This book reveals 49 PROVEN CHANGE MANAGEMENT PRINCIPLES and bite-size, easy-to-use techniques that work This book brings together 49 powerful "truths" about planning, driving, and sustaining organizational change: real solutions for the tough challenges faced by every business leader. You'll discover which skills you need most, and how to develop them ... how to lead change without eroding employee motivation, commitment, and productivity ... why you must start fast, and "run before you walk" ... when to persuade, when to educate, and when to "use force" ... how to make the change agenda everyone's agenda ... and how to create the right cultural framework for successful change. This isn't "someone's opinion." It's a definitive, evidence-based gui ...